AVALIAÇÃO DA EVOLUÇÃO DO ÍNDICE GERAL DE CURSOS - IGC DAS INSTITUIÇÕES DE ENSINO SUPERIOR DE SANTA CATARINA - Cleber Cervi (Universidade Federal de Santa Catarina, 2019)
The competitiveness in the education sector makes Higher Education Institution (HEI) to be attentive to the quality of service they offer, aiming to maintain and win new students, partners or investors. For many students, the institution's image and its perceived quality are the main criteria in choosing an HEI and it is transmitted, often, through the media that publishes rankings. Most rankings and indicators take into account the concepts of General Index of Courses - IGC, so HEI’s managers should be aware of them, looking for strategies to improve them, as they will be responsible for conveying the quality of HEIs and course. Thus, this study sought to determine the evolution of IGC of the Santa Catarina’s HEI from 2007 to 2014 and if has difference in the quality of public and private HEI, as well as to evaluate the difference between types of academic organization – namely university, university centers, colleges and federal institutes, in order to examine whether disclosure of such indicators really serves as a promoter of improvement in the quality of the HEI. Using data from the E-MEC system and with the help of statistical techniques it’s possible to conclude that (1) the evolution of the IGC was marginally significant in the analyzed period, (2) the universities have higher IGC than colleges only in three analyzed years, (3) the public’s HEI are superior of private’s HEI.